Chikungunya virus vector competency of Brazilian and Florida mosquito vectors - Honório, Nildimar Alves (PLoS Negl Trop Dis, 2018)
Chikungunya virus is a vector-borne alphavirus transmitted by the bites of infected female Ae. aegypti and Ae. albopictus. In Brazil between 2014 and 2016 almost 320 thousand autochthonous human cases were reported and in Florida numerous imported CHIKV viremic cases (> 3,800) demonstrate the potential high risk to establishment of local transmission. In the present study, we carried out a series of experiments to determine the viral dissemination and transmission rates of different Brazilian and Florida populations of Ae. aegypti and Ae. albopictus at 2, 5, and 13 days post-infection for the emergent Asian genotype of CHIKV. Our results show that all tested populations of Ae. aegypti and Ae. albopictus have a high proportion (> 0.80) of individuals with disseminated infection as early as 2 days-post exposure. We found no significant treatment effects of mosquito population origin effects on viral dissemination rates. Transmission rates had a heterogeneous pattern, with US Ae. aegypti and Brazilian Ae. albopictus having the highest proportion of individuals with successful infection (respectively 0.50 and 0.82 as early as 2 days-post infection). Model results found significant effects of population origin, population origin x species, population origin x days post-infection and population origin x species x days post infection.